Cytotoxic activity of peripheral blood mononuclear cells in patients with endometriosis: A cross-sectional study - Raden Muharam; Arleni Bustami; Indra Gusti Mansur; Teuku Zulkifli Jacoeb; Jerome Giustiniani; Valerie Schiavon; Armand Bensussan (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Endometriosis is believed to be associated with dysfunction of the lymphocyte population and cytotoxicity of natural killer (NK) cells, induced by the production of interleukin-2 (IL-2). Objective: This study aimed to investigate T lymphocytes and NK cell activity in the peripheral blood mononuclear cells (PBMCs) of women with endometriosis. Materials and Methods: PBMCs were obtained from the peripheral venous blood samples of 14 women with and without endometriosis (n = 7 for each group). Then, the PBMCs were co-cultured for 4 days and were treated with recombinant IL-2 for cytotoxic activity toward target cells (Daudi and K562 cells). The cytotoxicity activity was determined using the 51 chromium release assay before and after stimulation. Flow cytometry measurement was used to examine the expression of T lymphocytes and NK cells before and after being treated with IL-2. Results: The concentration of CD3+CD28+ (co-stimulatory) was significantly lower in the endometriosis group (65.62 ± 5.38) compared to in its counterpart (50.24 ± 4.22) (p = 0.04) before stimulation. However, no significant differences were observed in any other T lymphocytes and NK cells. It was also found that there was a significant increase of CD3-CD28+ after treatment with IL-2 only in the healthy control but not in women with endometriosis. Conclusion: Increased expression of CD160 and decreased CD28 play a role in inhibiting NK cell activation and T cell response in women with endometriosis.